Iron status of highly trained New Zealand triathletes - Ngawati, A.; Cummins, R. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
Previous research has shown that prolonged and strenuous physical training can induce changes in haematological indices of athletes. In particular, diminished iron status can have detrimental effects on performance. The aim of this study was to investigate the iron status of highly trained New Zealand triathletes.